(untitled) (Journal of Surgical Sciences, 2025)
Epidermoid inclusion cysts of the perineal region are a very rare entity, which require careful diagnosis by appropriate imaging and according management. We are here to describe an unusual case of a huge perineal epidermoid inclusion cyst extending upwards into pelvic cavity, which was removed successfully by meticulous dissection in abdominoperineal approach. Essential investigations to ensure accurate diagnosis in addition to surgical techniques followed to ensure complete removal & to prevent recurrence are described in this case report. Journal of Surgical Sciences (2021) Vol. 25 (1) : 53-57